A Bibliometric Analysis of Pesantren and Entrepreneurship - Irni Nuraini (SMART Insight, 2022)
The implementation of entrepreneurial education requires an appropriate ecosystem, and one of the institutions that can implement this education for students is the pesantren. This study seeks to assess the literature on pesantren and entrepreneurship by examining research trends and future directions. Using the VOSViewer application, two hundred nineteen articles from the journal Dimensions that were published between 2001 and 2023 were evaluated. The quantitative method was utilized for the bibliometric analysis, whilst the qualitative method was utilized for the literature review. This study's conclusions consist of four research clusters: Education and Curriculum of Pesantren Entrepreneurship, Model of Pesantren Entrepreneurship, Research Method of Pesantren and Entrepreneurship, and Pesantren and Community Development.